2020
DOI: 10.1159/000507250
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Roles of miR-3162-3p in Pulmonary Inflammation in Normal and Asthmatic Mice as well as Antagonism of miR-3162-3p in Asthma Treatment

Abstract: MicroRNA (miRNA) mimics or antagomirs hold great promise for asthma treatment compared with glucocorticoids as mainstay therapy for asthma. But the role of miRNA in regulating asthmatic inflammation is largely unclear. We previously reported that miR-3162-3p in the peripheral blood of children with asthma was obviously upregulated compared to that in healthy children. This study aimed to elucidate the role of miR-3162-3p in pulmonary inflammation in normal and asthmatic mice as well as preliminarily explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It has been shown that miRNA-3162-3p is associated with the increased production of active beta-catenin, intensifying the inflammatory process and hyperreactivity of the airways. The use of anti-miRNA-3162-3p was compared in the use of dexamethasone and resulted in the inhibition of the Wnt/beta-catenin pathway [55,56]. Similar results between the target Wnt/beta-catenin pathway and miRNA-3162-3p were observed in mice lung cells for miRNA-943-3p, and the antagomir application of this molecule [57].…”
Section: Mirnas and Pathways Responsible For The Development Of Asthm...mentioning
confidence: 73%
“…It has been shown that miRNA-3162-3p is associated with the increased production of active beta-catenin, intensifying the inflammatory process and hyperreactivity of the airways. The use of anti-miRNA-3162-3p was compared in the use of dexamethasone and resulted in the inhibition of the Wnt/beta-catenin pathway [55,56]. Similar results between the target Wnt/beta-catenin pathway and miRNA-3162-3p were observed in mice lung cells for miRNA-943-3p, and the antagomir application of this molecule [57].…”
Section: Mirnas and Pathways Responsible For The Development Of Asthm...mentioning
confidence: 73%
“…As shown in Figure 2, as the severity of AZ progressed, The research reported, the expression of miR-21 was upregulated in the lungs of mice stimulated with ovalbumin (OVA) compared to unstimulated mice, pulmonary eosinophils and mucus production were reduced in OVA-treated miR-21 knockout (KO) mice (17)(18)(19), furthermore, OVAtreated miR-21 KO mice showed markedly reduced bronchial hyperresponsiveness. MiR-21 may play a key role in Th2-related allergic conditions by regulating Th2 cells and cytokines (20)(21)(22). The miR-21 expression in CAMP was raised than that in healthy control children, at the cutoff value of 3.5, the sensitivity and specificity of miRNA-21 to distinguish CAMP from control children were 83%…”
Section: Blood Micro-rnas According To Az Severitymentioning
confidence: 94%
“…Further research has shown that the blood level of miR-3162-3p was significantly higher in children with asthma than in healthy children [ 34 ]. Inhibition of miR-3162-3p in OVA-induced asthmatic mice could effectively alleviate airway inflammation and bronchial hyperresponsiveness, decrease β-catenin expression, maintain Th1/Th2 balance and inhibit airway remodeling [ 34 ]. When allergic airway inflammation occurs, miR-1165-3p plays an effective role by targeting IL-13 and protein phosphatase, Mg2 + /Mn2 + -dependent 1A (PPM1A).…”
Section: Mirnas In Asthmamentioning
confidence: 99%